Edukasi EDUKASI MANAJEMEN BENCANA UNTUK MENINGKATKAN KESIAPSIAGAAN BENCANA PADA PELAJAR DI SMAN 2 LUWUK KABUPATEN BANGGAI: Disaster Management Education to Improve Disaster Preparedness among Students at SMAN 2 Luwuk, Banggai Regency - Mangemba, Dg; Alfrida Mangundap, Selvi; Kurniasari Yuwono, Dian; Subchan, Djadid; Hasan, Sri Musriniawati (Jurusan Keperawatan Politeknik Kesehatan Kementerian Kesehatan Palu, 2024)
Introduction: The Banggai region and the Banggai islands are in an area prone to earthquakes and tsunamis. The Bangai and Banggai Islands areas experienced an earthquake with a magnitude of 6.9 on the SR which shocked the residents of Luwuk and caused a lot of damage. The aim of this service activity is to increase community preparedness, in this case students, in facing disasters. The methods used in this community service are lectures, questions and answers, and discussions. The tools and media used in this PKM are questionnaires, laptops, LCDs, screens and disaster management leaflets. The questionnaire contains questions related to health education material about disaster management which will be given to pre- and post-education respondents. Results: There were 94 participants in the activity, consisting of 6 teachers and 88 students. There was an increase in the proportion of participants with good knowledge of disaster management from 62.5% to 90%. The question item that shows the greatest improvement in knowledge is about important numbers that need to be known regarding disasters and signs of a tsunami. The suggestion from this activity is the need to improve education on disaster preparedness management for students at SMAN 2 Luwuk by increasing outreach and training activities related to disasters so that students are prepared to face disasters.